8
$\begingroup$

I am starting to feel more confident in my understanding of Ramanujan's proof of Bertrand's postulate. I hope that I am not getting overconfident.

In particular, Ramanujan's does the following comparison in step (8):

$$\ln\Gamma(x) - 2\ln\Gamma(\frac{x}{2} + \frac{1}{2}) \le \ln(\lfloor{x}\rfloor!) - 2\ln(\lfloor\frac{x}{2}\rfloor!)$$

It occurs to me that this can be generalized to:

$$\ln\Gamma(\frac{x}{b_1}) - \ln\Gamma(\frac{x}{b_2} + \frac{1}{2}) - \ln\Gamma(\frac{x}{b_3} + \frac{1}{2})\le \ln(\lfloor\frac{x}{b_1}\rfloor!) - \ln(\lfloor\frac{x}{b_2}\rfloor!) - \ln(\lfloor\frac{x}{b_3}\rfloor!)$$

when:

$$\frac{x}{b_1} = \frac{x}{b_2} + \frac{x}{b_3}$$

I would really appreciate it if my argument could be reviewed and someone could call out any mistakes either in the answer or in comments. :-)

Here's the argument for this generalization:

Let:

$$\{\frac{x}{b_i}\} = \frac{x}{b_i} - \lfloor\frac{x}{b_i}\rfloor$$

where:

$$0 \le \{\frac{x}{b_i}\} < 1$$

Since:

$$\{\frac{x}{b_1}\} + \lfloor\frac{x}{b_1}\rfloor = \{\frac{x}{b_2}\} + \lfloor\frac{x}{b_2}\rfloor + \{\frac{x}{b_3}\} + \lfloor\frac{x}{b_3}\rfloor$$

We have:

$$\{\frac{x}{b_1}\} \le \{\frac{x}{b_2}\} + \{\frac{x}{b_3}\}$$

So that:

$$-\{\frac{x}{b_1}\} \ge -\{\frac{x}{b_2}\} + -\{\frac{x}{b_3}\}$$

$$2-\{\frac{x}{b_1}\} \ge 1-\{\frac{x}{b_2}\} + 1-\{\frac{x}{b_3}\}$$

$$1-\{\frac{x}{b_1}\} \ge 1-\{\frac{x}{b_2}\} - \frac{1}{2} + 1-\{\frac{x}{b_3} \} - \frac{1}{2}$$

$$\lfloor\frac{x}{b_1}\rfloor + 1 - \frac{x}{b_1} \ge (\lfloor\frac{x}{b_2}\rfloor + 1 - \frac{x}{b_2} - \frac{1}{2}) + (\lfloor\frac{x}{b_3}\rfloor + 1 - \frac{x}{b_3} - \frac{1}{2})$$

$$\lfloor\frac{x}{b_1}\rfloor + 1 \ge (\lfloor\frac{x}{b_2}\rfloor + 1) + (\lfloor\frac{x}{b_3}\rfloor + 1)$$

If $\Delta{t_1} \ge \Delta{t_2} + \Delta{t_3}$ and $x_1 + \Delta{t_1} \ge x_2 + \Delta{t_2} \ge x_3 + \Delta{t_3} > 0$,

Using the logic in the answer here:

$$\frac{\Gamma(x_1 + \Delta{t_1})}{\Gamma(x_1)} \ge \frac{\Gamma(x_2 + \Delta{t_2})}{\Gamma(x_2)}\frac{\Gamma(x_3 + \Delta{t_3})}{\Gamma(x_3)}$$

Let:

$x_1 = \frac{x}{b_1}$, $\Delta{t_1} = 1 - \{\frac{x}{b_1}\}$,

$x_2 = \frac{x}{b_2}+\frac{1}{2}$, $\Delta{t_2} = \frac{1}{2} - \{\frac{x}{b_2}\}$

$x_3 = \frac{x}{b_3}+\frac{1}{2}$, $\Delta{t_3} = \frac{1}{2} - \{\frac{x}{b_3}\}$

where $\frac{x}{b_2} \ge \frac{x}{b_3}$ (Otherwise, switch the two values).

Then:

$$\frac{\Gamma(\lfloor\frac{x}{b_1}\rfloor+1)}{\Gamma(\frac{x}{b_1})} \ge \frac{\Gamma(\lfloor\frac{x}{b_2}\rfloor+1)}{\Gamma(\frac{x}{b_2} + \frac{1}{2})}\frac{\Gamma(\lfloor\frac{x}{b_3}\rfloor+1)}{\Gamma(\frac{x}{b_3}+\frac{1}{2})}$$

So then it follows:

$$\ln\Gamma(\lfloor\frac{x}{b_1}\rfloor + 1) - \ln\Gamma(\frac{x}{b_1}) \ge \ln\Gamma(\lfloor\frac{x}{b_2}\rfloor + 1) - \ln\Gamma(\frac{x}{b_2} + \frac{1}{2}) + \ln\Gamma(\lfloor\frac{x}{b_3}\rfloor + 1) - \ln\Gamma(\frac{x}{b_3} + \frac{1}{2})$$

And we have shown:

$$\ln\Gamma(\frac{x}{b_1}) - \ln\Gamma(\frac{x}{b_2}+\frac{1}{2}) - \ln\Gamma(\frac{x }{b_3}+\frac{1}{2}) \le \ln(\lfloor\frac{x}{b_1}\rfloor!) - \ln(\lfloor\frac{x}{b_2}\rfloor!) - \ln(\lfloor\frac{x}{b_3}\rfloor!)$$

Please let me know if you see any mistakes.

Thanks,

-Larry


Edit: Based on reviewing Zander's answer, I believe that this argument can be saved. The revision requires two separate arguments:

  • one for: $\{\frac{x}{b_2}\} + \{\frac{x}{b_3}\} \ge 1$
  • another for: $\{\frac{x}{b_2}\} + \{\frac{x}{b_3}\} < 1$

The link for the first argument is here. The link for the second argument is here.

$\endgroup$
10
$\begingroup$

After this step: $$ \lfloor\frac{x}{b_1}\rfloor + 1 - \frac{x}{b_1} \ge (\lfloor\frac{x}{b_2}\rfloor + 1 - \frac{x}{b_2} - \frac{1}{2}) + (\lfloor\frac{x}{b_3}\rfloor + 1 - \frac{x}{b_3} - \frac{1}{2}) $$ we have $$ \lfloor\frac{x}{b_1}\rfloor + 1 \ge (\lfloor\frac{x}{b_2}\rfloor + 1) + (\lfloor\frac{x}{b_3}\rfloor + 1)-1 $$ but what you have is incorrect. For example, let $x=77.1,b_1=6,b_2=7,b_3=42$, then $\lfloor x/b_1\rfloor=12, \lfloor x/b_2\rfloor=11, \lfloor x/b_3 \rfloor=1$ and $13\not\ge 14$.

And in this case your inequality is also violated: $$ \ln \Gamma\left(\frac{77.1}{6}\right)-\ln\Gamma\left(\frac{77.1}{7}+\frac{1}{2}\right)-\ln \Gamma\left(\frac{77.1}{42}+\frac{1}{2}\right) = 3.10698\cdots \\ \ge \ln(12!)-\ln(11!)-\ln(1!) = 2.4849\cdots $$

$\endgroup$
  • $\begingroup$ Thanks very much! I'll keep investigating to see if I can save any part of the argument. Cheers. :-) $\endgroup$ – Larry Freeman Apr 14 '13 at 3:17
  • 2
    $\begingroup$ After reviewing the issue, I believe that the proof can be saved. I believe that the step in question is valid in the case where $\{\frac{x}{b_2}\} + \{\frac{x}{b_3}\} \ge 1$. Then, the step in question becomes $\lfloor\frac{x}{b_1}\rfloor - \frac{x}{b_1} = (\lfloor\frac{x}{b_2}\rfloor + 1 - \frac{x}{b_2} - {1}{2}) + (\lfloor\frac{x}{b_3}\rfloor + 1 - \frac{x}{b_3} - \frac{1}{2})$ which works. For example, let $x=78.9$ and $\lfloor\frac{x}{b_1}\rfloor+1\ge(\lfloor\frac{x}{b_2}\rfloor+1)+(\lfloor\frac{x}{b_3}\rfloor+1)$. To avoid confusion, I'll post a new question with a revised proof. $\endgroup$ – Larry Freeman Apr 14 '13 at 10:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.